GAMBARAN MOTIVASI MASYARAKAT TERHADAP PERAWATAN GIGI DITINJAU DARI ANGKA PERFORMANCE TREATMENT INDEX - Rawati Siregar; Sri Junita Nainggolan; Netty Jojor Aritonang (Poltekkes Kemenkes Medan, 2022)
Performance Treatment Index is a number that shows the ability to maintain teeth by filling teeth. Tooth filling is a treatment action by placing a filling in the cavity of the tooth (caries). The purpose of dental fillings is to prevent further damage, restore the anatomy and function of the teeth to their original state to prevent tooth extraction. This type of research is a descriptive survey. The research sample was the community with a total of 30 respondents. The purpose of the study was to determine the community's motivation about dental care to the Performance Treatment Index (PTI) number. The results showed that the respondent's motivation regarding dental care was in the good category (66.67%), the dental condition status with DMF-T was 8.46 on average, D=4, M=4, F=0.47. Compared to the health status indicator (D?2), the D value in this study was above the target. The PTI achievement rate is 5.5% compared to the dental health level indicator (PTI?50%), so the PTI value is below the target. It is hoped that the community will try to maintain their teeth by filling their teeth according to indications, conducting regular dental check-ups every 6 months and maintaining dental and oral health.